Preparing the “New” Biologist of the Future: Student Research at the Interface of Mathematics and Biology - Duncan, Sarah I. (American Society for Cell Biology, 2010)
We describe a unique Research Experience for Undergraduates and Research Experience for Veterinary students summer program at the National Institute for Mathematical and Biological Synthesis on the campus of the University of Tennessee, Knoxville. The program focused on interdisciplinary research at the interface of biology and mathematics. Participants were selected to work on projects with a biology mentor and a mathematics mentor in an environment that promoted collaboration outside of the students' respective disciplines. There were four research projects with teams of four participants and two faculty mentors. The participants consisted of a mixture of 10 undergraduates in biology- and mathematics-related disciplines, four veterinary students, and two high-school teachers. The activities included lectures on both the biological and mathematical backgrounds of the projects, tutorials for software, and sessions on ethics, graduate school, and possible career paths for individuals interested in biology and mathematics. The program was designed to give students the ability to actively participate in the scientific research process by working on a project, writing up their results in a final report, and presenting their work orally. We report on the results of our evaluation surveys of the participants.